Numerical study of reservoir cooling by means of peltier effect - Farias, Rodrigo Martins (2012)
Submitted by Suria Alves (suriaalves@yahoo.com.br) on 2011-12-01T09:26:27Z No. of bitstreams: 1 Numerical study of reservoir cooling by means of peltier effect.pdf: 1767945 bytes, checksum: 93271c9e39c021e9c7aaa8277eb6371b (MD5)